Bifurcation lesions: Are new strategies and devices needed? Bifurkationsläsionen: Braucht es neue Strategien und Devices? - Gaede, Luise (Herz, 2022)
Interventional treatment of bifurcation lesions, especially true complex bifurcation lesions, continue to be a challenge for interventional cardiologists. A primary one stent strategy is always preferred for simple bifurcation lesions, whereas studies in recent years have shown that a two stent strategy may be advantageous for true bifurcations, i.e. those involving at least the distal main branch as well as the side branch. This seems to be even more pronounced when the lesion presents as complex, i.e., the side branch shows high-grade stenosis over longer stretches and the complete lesion fulfils certain criteria, e.g., severe calcification and a bifurcation angle < 45° or > 70°. According to the latest randomized trials and meta-analyses, the double kissing (DK) crush and double kissing mini-crush (DKMC) techniques in particular seem to be advantageous for these lesions; however, in recent years the established techniques have been continuously refined and further developed. The DK culotte technique and the nano-crush technique deserve special attention. Both techniques seem to further improve and simplify the existing underlying strategies; however, further studies to prove the superiority of these techniques over the established ones are still pending. Overall, the implementation of the available randomized study results, the further development of the techniques and also of the materials can continuously improve the outcome of the patients after interventional treatment of bifurcation lesions. This is also confirmed by the latest registry data, which for the first time could show equal event rates in patients after treatment of complex lesions compared to simple lesions in the clinical practice.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Coronary vessels; Culotte technique; DK crush technique; Stent strategies; Stent techniques